Use of online interactive tools in an open distance learning context: Health studies students' perspective* - Kefiloe A. Maboe (AOSIS, 2017)
Background: Open distance learning (ODL) institutions provide educational challenges with specific reference to the training of nurses. They have adopted online technologies to facilitate teaching and learning. However it is observed that most nurses do not use or minimally use tools such as a discussion forum for online interaction to facilitate teaching and learning. Objective: The purpose of this study was to determine how the discussion forum as an online interactive tool be used in an ODL institution to enhance student-to-student and student-to-lecturer online interactions. Design: Quantitative and descriptive in nature. Method: No sampling was done. An online questionnaire was sent to all 410 second and third years Health Services Management students around the world registered with a specific ODL institution during the second semester. Eighty seven students responded to the questionnaire. Data analysis was done quantitatively and descriptively in the form of diagrams. Results: The findings indicated that 84.9% of students own computers, and 100% own cellular phones, but only 3.8% participated in online discussion forum. Some students indicated that they were technologically challenged. Some lecturers interact minimally online and are not supportive to them. The institution does not give them the support they need to acquire the necessary skills to utilise these technologies. Conclusion: The article suggests that lecturers, active interaction in an online discussion forum as a way of supporting students, are fundamental to effective teaching and learning.The university should consider providing intensive mentoring to students to enable them to utilise the available technologies optimally.